Comprehensive Overview of Carbohydrate Polymers - Mr.Harshal K Patil; Akash S. Jain; Divakar R. Patil; Azam Z. Shaik; Sameer R. Shaik; Sunil P. Pawar (International Journal of Membranes, 2024)
Targeting drug delivery specifically to the colon has become increasingly crucial for treating various colonic diseases like colorectal cancer, amebiasis, ulcerative colitis, and Crohn’s disease. Numerous strategies have been developed for this purpose, including using enzymatically degradable polymers, employing prodrug-based approaches, coating drugs with polymers sensitive to time or pH changes, utilizing osmotically and pressure-controlled delivery systems. Polysaccharides activated by the colon's physiological environment show significant potential as they offer enhanced site specificity and address therapeutic requirements effectively. However, delivery systems relying solely on a single polysaccharide often fail to ensure precise targeted release due to variations in pH and transit time among individuals and disease states. Traditional methods often result in premature drug release. To overcome these challenges, combining or chemically modifying polysaccharides has been explored, effectively mitigating the limitations associated with single polysaccharide use. This review explores emerging approaches in this field, reexamines current technologies, and outlines future developments.
Keywords: Colonic diseases; Enzymatically degradable polymers; Polysaccharides; Site specificity; Targeted drug delivery